Sectoral Credit Allocation of Deposit Money Banks and Poverty Reduction in Nigeria (International Journal of Business, Economics and Management, 2019)
The nature of relationship between deposit money banks loan to certain sector of the economy and its possible effect of reducing poverty rate in Nigeria is controversial and significant. As such, this study set out to examine the extent to which deposit money bank loan and advances to SMEs, agricultural, and manufacturing sectors in Nigeria has helped in reducing poverty rate. To achieve the objective of the study, unit root test, auto regressive distributive lag estimate and causality test were employed. Result shows that deposit money bank loan to SMEs and agricultural sector seem to be inversely related to poverty rate in Nigeria while sectoral allocation to the manufacturing sector is not capable of reducing poverty rate in Nigeria. This inherent relationship between loans to manufacturing sectors and poverty reduction in Nigeria could be attributed to some structural factors cited in the body of the paper. In the light of these findings, this study concluded that (i) Poverty rate in Nigeria is significantly sensitive to deposit money bank credit to agricultural sector; (ii) Within the context of the study, deposit money bank allocation to SMEs has helped in reducing poverty rate in Nigeria to the tune of 1.821 unit. On this premises, it is recommended that bank ordinances and financial institution act should be review to ensure that more credit is allocated to agricultural and SMEs sector as this will help in reducing the ever teaming trend of poverty in Nigeria through the window of job creation.